Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.4028/www.scientific.net/amr.255-260.1048
|View full text |Cite
|
Sign up to set email alerts
|

The Rehabilitation Project of Highland Road Tunnel

Abstract: This paper presents the rehabilitation project of Dabanshan highland road tunnel. Cause analysis is carried by insight into the information of climate, geological, hydrological condition, tunnel defects type and parameters. Water leakage, low temperature and poor rock condition are considered to be source of tunnel defects, and the essential of rehabilitation of highland road tunnel are water leakage treatment and heat preservation system reinstatement. Measures taken to solve the problems of cracks, water lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The water trough is introduced into the natural gully with good geological conditions and stable surrounding rocks through the discharge tunnel, and the application effect is ideal. (2) Field investigation on the cold-proof drainage hole of tunnels in service in the cold region and evaluation on its effect: Liu et al [35] conducted disease detection on the tunnel at Dabanshan, which has been put into operation, and confirmed the effective function of groundwater in the cold-proof drainage tunnel drainage hole by analyzing the causes of the disease. (3) Simulation study for temperature field of cold-proof drainage hole: Lai [36] conducted onsite temperature monitoring on the Qingshashan highway tunnel in the eastern Tibetan Plateau and studied the temperature difference distribution of the tunnel in the cold region.…”
Section: State Of the Artmentioning
confidence: 99%
“…The water trough is introduced into the natural gully with good geological conditions and stable surrounding rocks through the discharge tunnel, and the application effect is ideal. (2) Field investigation on the cold-proof drainage hole of tunnels in service in the cold region and evaluation on its effect: Liu et al [35] conducted disease detection on the tunnel at Dabanshan, which has been put into operation, and confirmed the effective function of groundwater in the cold-proof drainage tunnel drainage hole by analyzing the causes of the disease. (3) Simulation study for temperature field of cold-proof drainage hole: Lai [36] conducted onsite temperature monitoring on the Qingshashan highway tunnel in the eastern Tibetan Plateau and studied the temperature difference distribution of the tunnel in the cold region.…”
Section: State Of the Artmentioning
confidence: 99%
“…Engineering practice has demonstrated that tunnels built in cold regions are susceptible to serious frost damage due to periodic temperature changes (Wang et This poses mechanical and technical challenges ) as well as signi cant safety hazards to the tunnel's operation and maintenance (Li et al 2022;Liu et al 2011). The primary issues associated with frost damage in high-altitude tunnels are ice accumulation on the lining structure and auxiliary facilities, ice blockage in drainage ditches, ice buildup on the roadbed, and structural cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al 15 studied the causes of water seepage in alpine cold tunnels by developing new tunnel drainage structures. Liu et al 16 introduced the basic principles, ideas, and specific measures for the treatment of diseases such as water leakage, insulation, and lining reinforcement in the Dabanshan cold Tunnel by analyzing the causes of the diseases of tunnels. To reduce the risk of blockage in the tunnel drainage system, Liu et al 17 determined the distribution of defects in highway tunnels through on-site investigation, indoor experiments, and literature analysis, and proposed an optimization method for tunnel drainage structure.…”
Section: Introductionmentioning
confidence: 99%